2016
DOI: 10.1007/s00253-016-7895-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel GH6 cellobiohydrolase from Paenibacillus curdlanolyticus B-6 and its synergistic action on cellulose degradation

Abstract: We recently discovered a novel glycoside hydrolase family 6 (GH6) cellobiohydrolase from Paenibacillus curdlanolyticus B-6 (PcCel6A), which is rarely found in bacteria. This enzyme is a true exo-type cellobiohydrolase which exhibits high substrate specificity on amorphous cellulose and low substrate specificity on crystalline cellulose, while this showed no activity on substitution substrates, carboxymethyl cellulose and xylan, distinct from all other known GH6 cellobiohydrolases. Product profiles, HPLC analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 50 publications
2
16
0
7
Order By: Relevance
“…4). As previously reported, some cellobiohydrolases of GH6 were detected to hydrolyze CMC-Na, as well as PASC, which were defined as the exo-/endo-type cellobiohydrolases (Wang et al, 2013;Baramee et al, 2016). In exo-/endo-type cellobiohydrolases, the flexible tunnel-like active sites are the reason that causing exo-type action connected with endo-type action.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…4). As previously reported, some cellobiohydrolases of GH6 were detected to hydrolyze CMC-Na, as well as PASC, which were defined as the exo-/endo-type cellobiohydrolases (Wang et al, 2013;Baramee et al, 2016). In exo-/endo-type cellobiohydrolases, the flexible tunnel-like active sites are the reason that causing exo-type action connected with endo-type action.…”
Section: Discussionmentioning
confidence: 57%
“…Similar conclusion was reported on GH9 endoglucanase CenC from Clostridium thermocellum and β-glucosidase Bgl4 from Penicillium funiculosum (Haq et al, 2015;Ramani et al, 2015), owing to bivalent metallic cations could increase the stability and cause conformational changes of catalytic center of cellulose. The observation of substrate specificity showed that CtCel6 displayed high activity towards β-D-glucan with 1.27 U/mg, which was higher than two cellobiohydrolase (CBHI, CBHII) from Trichoderma viride (Song et al, 2010), but lower than cellobiohydrolase PcCel6A from Paenibacillus curdlanolyticus (Baramee et al, 2016). PASC could also be hydrolyzed by CtCel6 as showed in Table 2.…”
Section: Discussionmentioning
confidence: 96%
“…The processive endo-␤-1,4-glucanase CtCel9R, from C. thermocellum, produced cellotetraose as a primary hydrolysis product and slowly but further hydrolyzed it to smaller oligosaccharides, while the ␤-glucosidase TbCglT, from T. brockii, was capable of rapidly converting cellobiose and short-chain cellooligosaccharides to glucose. These two enzymes demonstrated high thermostability and high glucose tolerance (19). Since the biorefineries generally employ high temperatures (2), these two enzymes were selected for glucose production from the pretreated rice straws, including XRS, ARS, and SXRS.…”
Section: Resultsmentioning
confidence: 99%
“…strain LD-1 (35) and Pleurotus ostreatus (36), with commercial Trichoderma viride cellulase ONOZUKA 3S and Aspergillus niger cellulase Y-NC, resulted in 18.6% and 32.0% glucose yields, respectively, which were lower than the values obtained by saccharification of all of the treated rice straws by the combination of CtCel9R and TbCglT (Table 3). These results may be ascribed to higher glucose tolerance and thermostability (19) and lower affinity for lignin of bacterial cellulases CtCel9R and TbCglT than fungal cellulases, and these factors together may have shown their best performance in cellulose saccharification. Therefore, the combination of CtCel9R and TbCglT is a great formulation in the saccharification of cellulose to generate glucose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation